Critical HRD—Need for Emergence of Critters in Adult Education - Jeffrey M. Keefer; Robin Yap (Adult Education Research Conference, 2007)
Critters seek to expose, understand, and change the underlying causes of a phenomenon—the business of adult education. Adult education is foundational to the engagement of critical management studies (CMS). Critical HRD appears to be a bridge between CMS frameworks and Adult Education theories. Critters will ensure the complexities and breadth of influences get threaded for all stakeholders.